2018
DOI: 10.1016/j.socscimed.2018.07.046
|View full text |Cite
|
Sign up to set email alerts
|

The use of video vignettes to measure health worker knowledge. Evidence from Burkina Faso

Abstract: The quality of care is a crucial determinant of good health outcomes, but is difficult to measure. Survey vignettes are a standard approach to measuring medical knowledge among health care providers. Given that written vignettes or knowledge tests may be too removed from clinical practice, particularly where "learning by doing" may be an important form of training, we developed a new type of provider vignette. It uses videos presenting a patient visiting the clinic with maternal/early childhood symptoms. We te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…From this study we were able to collect data of the doctor’s behavior while controlling for other factors such as patient differences. Previous studies investigated the possibility of patient vignettes in measuring health worker knowledge [40] and evaluating the effect of clinical decision support systems for improving hospital discharge decision-making [41, 42]. Furthermore, the concealment of the real purpose of the study and presenting the aim of the experiment to the doctors as a project to collect prescription data allowed this study to avoid strategic response biases by the doctors who might oppose payment schemes that disconnects the remuneration of doctors from the volume of medical service.…”
Section: Discussionmentioning
confidence: 99%
“…From this study we were able to collect data of the doctor’s behavior while controlling for other factors such as patient differences. Previous studies investigated the possibility of patient vignettes in measuring health worker knowledge [40] and evaluating the effect of clinical decision support systems for improving hospital discharge decision-making [41, 42]. Furthermore, the concealment of the real purpose of the study and presenting the aim of the experiment to the doctors as a project to collect prescription data allowed this study to avoid strategic response biases by the doctors who might oppose payment schemes that disconnects the remuneration of doctors from the volume of medical service.…”
Section: Discussionmentioning
confidence: 99%
“…We follow previous studies 14,16,17 and include a vector of control variables, denoted Cov, for cadre of healthcare professional, work experience, and facility type. For example, previous evidence show that higher cadres have higher competence and that work experience could have a negative effect on competence.…”
Section: Methodsmentioning
confidence: 99%
“…Client satisfaction may also better reflect patients' perceptions of respect and courtesy than the facility's adherence to medical protocols. 14 It has been shown that poor clinical knowledge is a greater constraint across African countries than other components of the healthcare system, such as drug availability or health worker absenteeism. 8 Clinical knowledge is a key measure of the quality of treatment as it indicates the highest level of quality of care the provider would be able to deliver assuming access to relevant medical infrastructure and adequate incentive mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In recent work in Burkina Faso, researchers developed video vignettes of patients presenting maternal or early childhood symptoms (Banuri et al 2018). These vignettes were locally developed and featured a local actor, who described complications like pre-term labor or mastitis.…”
Section: Measuring the Quality Of Clinical Practicementioning
confidence: 99%
“…Health workers may thus skip elements of care they think the patient cannot pay for or that may require higher levels of effort-for instance, an explanation of what a particular test accomplishes-to provide to the poor. Related results from a lab-in-the-field experiment in Burkina Faso suggest that providing care to the poor requires higher levels of effort from providers because the poor might have lower healthrelated knowledge or present more complex health conditions (Banuri et al 2018). However, consistent with the finding that idle capacity does not vary with patient wealth, the data suggest that idle capacity is similar across patient wealth quintiles in all the countries studied.…”
Section: Correlates Of the Know-can-do Gapmentioning
confidence: 99%